PENGARUH DURASI SHOT PEENING TERHADAP STRUKTUR MIKRO DAN KEKERASAN PERMUKAAN PADA AISI 316L - Rizqi Ilmal Yaqin; Priyo Tri Iswanto; Bambang Hari Priyambodo; Erich Umbu Kondi M (Institut Teknologi Dirgantara Adisutjipto, 2017)
Stainless steel 316L is widely used in medical applications. AISI 316L has good mechanical properties, good corrosion resistance and easy fabrication. On the other hand, 316L should be upgraded its surface mechanical properties for implantable materials. One of the treatment used is shot peening. shot peening can increase surface hardness in the presence of micro structure changes. These changes are due to plastic deformation and residual stress. This study discusses the effect of shooting time duration of 2, 4, 10, 20, and 30 against the micro structure and surface hardness. The steel balls used are 0.6mm in diameter and 40-50 HRC hardness with 8 bar pressure during shooting. the results of surface hardness on the duration of 2, 4, 10, 20, and 30 minutes obtained respectively are 296.7 HV, 380.8 HV, 425.8 HV, 445.0 HV, 504.9 HV and 523.1 HV. The surface hardness is increased due to structural changes on the surface and sub-surface of the shot peening material. The result of micro structure obtained is that with increasing duration of shot peening and the increasing of hardness value of surface hence grain size at sub surface that is smaller after treatment. Shot peening caused hardness of material 316L stainless steel and made grain of microstructure sub layer.